Perlindungan Hukum Terhadap Anak Sebagai Korban Dari Tindak Pidana Perdagangan Orang Di Kota Pekanbaru - Syaifullah Yophi Ardianto (Jurnal Ilmu Hukum, 2013)
Section 28 A of Constitution 1945 sounding: each and everyone is entitled to live and also is entitled to live on and his life and section 28 B article 2 Constitution 1945 sounding: every child are entitled to for continuity of life, grow, and expand and also are entitled to for protection from hardness and discrimination. The continued development of the time so the more crime is happening. One example of a crime that happened recently is the trafficking of children Several factors are behind the trafficking of children in the city of Pekanbaru, among which are economic factors, environmental factors, and education factors.